PELARGONIUM GRAVEOLENS (L'HÉR) ESSENTIAL OIL, ANTIOXIDANTS, ANTICYANOBACTERIAL AND ANTIALGAL COMPOUNDS: A SOLAR-BASED EXTRACTION TECHNIQUE AND YIELD PREDICTION USING LINEAR REGRESSION - ezzarrouqy, kamal (Food and Feed Research, 2026)
Solar hydro-distillation (SHD) is presented as a new green technique to effectively extract the various phytochemicals from food by-products. To better understand the procedure, results, and advantages of such a green and sustainable source, the goal of this study was to compare the efficiency of SHD to extract essential oils from Pelargonium graveolens (L'Hér) while simultaneously releasing antioxidant compounds like polyphenols and flavonoids in the remaining phase of the solar still. The yields of the essential oils were 0.64 % and 0.60 % for SHD and conventional hydro-distillation (CHD), respectively. By using GC-MS analysis, 52 volatile components were identified. Citronellol (27.54 %–26.51 %), citronellyl formate (13.63 %–11.33 %), geraniol (11.94 %–10.97 %) and geranyl formate (8.31 %–5.84 %) represented the main components for SHD and CHD oils, respectively. For the extracts produced by SHD and maceration, total phenolic compounds (TPC), total flavonoid compounds (TFC), and antioxidant activity (AA) based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity were evaluated. The results showed that the SHD extract produced an extremely good extraction yield in TPC, TFC, and IC50 (249.72 mg EAG.g-1 DM, 205.88 mg EQ.g-1 DM, and IC50=6.54 μg.mL-1, respectively). Moreover, HPLC-UV analyses showed conservation in the extract after the SHD process of some identified compounds such as tyrosol (31.71 mg.g-1 DM), gallic acid (24.67 mg.g-1 DM), protocatechuic acid (22.59 mg.g-1 DM), and ferulic acid (21.04 mg.g-1 DM). On the other hand, the essential oil and the extract prepared by SHD showed an important anti-cyanobacterial/anti-algal activity against the bacterial/algal strain tested Microcystis aeruginosa and Chlorella sp., with growth inhibition diameters of 15.43 ± 0.32 mm, 16.73 ± 0.40 mm and 17.13 ± 0.35 mm, 25.96 ± 0.15 mm, respectively for essential oil and extract. A positive linear correlation was observed between antioxidants, polyphenols, flavonoids and anti-cyanobacterial/anti-algal activity for solar extracts. Results showed that SHD is a good alternative for recovering bioactive compounds from the Pelargonium graveolens (L'Hér.) with potent antioxidant, and anti-cyanobacterial/anti-algal activity.
Keywords: geranium; solar hydro-destillation; essential oil; total phenolics/flavonoids; antioxidant activity; Microcystis aeruginosa; Chlorella